Studies on conducting polymer electroactive paper actuators: effect of humidity and electrode thickness - Deshpande, S. D.; Kim, Jaehwan; Yun, Sung-Ryul (Smart Materials & Structures, 2005)
Actuators based on cellulose paper with conducting polymer (CP-EAPap) as an electrode material were constructed. The bilayer and trilayer types of actuators were fabricated by depositing conducting polypyrrole on one side and two sides of cellophane paper respectively, which was previously gold coated. By varying the deposition time, the electrode thickness was manipulated. The performance of these two types of actuators was compared with respect to humidity changes and thickness variation. The electrode thickness plays a key role in the displacement behavior of these types of actuators. The best performance at higher humidity is also characteristic of CP-EAPap actuators. The possible mechanism of actuation is addressed in this paper.